Exendin-4(1-32)K-Capric Acid, a Glucagon-Like Peptide-1 Receptor Agonist, Suppresses Food Intake via Arcuate Pro-Opiomelanocortin Neurons - Sujin Yoo; Eun-Seon Yoo; Jae Il Kim; Jong-Woo Sohn (Endocrinology and Metabolism)
Background Glucagon-like peptide-1 (GLP-1) is an incretin known for its anti-obesity effects, and several effective drugs targeting GLP-1 receptors (GLP-1Rs) have recently been developed to treat obesity. Although GLP-1Rs are expressed by various populations of central neurons, it is still unclear which specific populations mediate the anti-obesity effects of GLP-1R agonists. Methods In this study, we utilized the previously reported GLP-1R agonist, exendin-4(1-32)K-capric acid (Ex-4c), and conducted whole-cell patch-clamp recordings, immunohistochemistry experiments, and in vivo food intake measurements. Results Our findings indicate that the appetite-suppressing effects of Ex-4c depend on pro-opiomelanocortin (POMC) neurons. Fos immunochemistry experiments and whole-cell patch-clamp recordings showed that Ex-4c activated POMC neurons in the arcuate nucleus of the hypothalamus. Additionally, we observed that Ex-4c stimulated GLP-1Rs and activated the protein kinase A (PKA)-dependent signaling pathway, which in turn closed putative adenosine triphosphate-sensitive K+ (KATP) channels, leading to the depolarization of POMC neurons. Conclusion Our results demonstrate that the appetite-suppressing effects of Ex-4c are mediated through the activation of arcuate POMC neurons. Furthermore, the PKA-dependent closure of putative KATP conductance is identified as the cellular mechanism responsible for the activation of POMC neurons.